Droplets pinned at chemically inhomogenous substrates: A simulation study of the two-dimensional Ising case - Trobo, Marta Liliana (2016)
As a simplified model of a liquid nanostripe adsorbed on a chemically structured substrate surface, a two-dimensional Ising system with two boundaries at which surface fields act is studied. At the upper boundary, the surface field is uniformly negative, while at the lower boundary (a distance L apart), the surface field is negative only outside a range of extension b, where a positive surface stabilizes a droplet of the phase with positive magnetization for temperatures T exceeding the critical temperature Tw of the wetting transition of this model. We investigate the local order parameter profiles across the droplet, both in the directions parallel and perpendicular to the substrate, varying both b and T. Also, precursor effects to droplet formation as T approaches Tw from below are studied. In accord with theoretical predictions, for T>Tw the droplet is found to have the shape of a semiellipse, where the width (distance of the interface from the substrate) scale is proportional to b (b1/2). So, the area of the droplet is proportional to b3/2, and the temperature dependence of the corresponding prefactor, which also involves the interfacial stiffness, is studied.